Learning Strategies at SD Muhammadiyah 5 Porong During Covid-19 Pandemic - Shafa Nurul Nabilah; Muhlasin Amrullah (Proceedings of The ICECRS, 2021)
The impact of the Corona virus disease 2019 (Covid-19) pandemic is now starting to spread to the world of education. This is done as an effort to prevent the spread of Covid-19. It is hoped that all educational institutions will not carry out activities as usual. This can reduce the spread of Covid-19. Schools, colleges and universities are closed to control the spread of the coronavirus. School closures bring convenience to students, teachers and parents. So, distance learning is a solution for continuing education system. However, the lack of network infrastructure, computers, and internet access poses a distance learning challenge in developing countries. The purpose of this study was to analyze learning strategies at SD Muhammadiyah 5 Porong in overcoming learning difficulties during this COVID-19 period. The research location is in SD Muhammadiyah 5 Porong. The research design is to use qualitative methods. The result of the research is that teachers carry out online learning systems by utilizing the development of internet applications, such as Zoom and Whatsapp. The conclusion of the study is that during the pandemic, SD Muhammadiyah 5 Porong has set an online learning strategy during the pandemic.